Brand development in women farmers group empowerment to support the tropical fruit tree community biodiversity management: A study from Garcinia sp conservation in Sijunjung, West Sumatra, Indonesia - Marendra Kiloes, Adhitiya (Indonesian Center for Horticulture Research and Development, 2019)
Presented by Adhitiya Marendra Kiloes (Indonesian Center for Horticulture Research and Development)), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.